D-Serine Metabolism and Its Importance in Development of Dictyostelium discoideum - Ito, Tomokazu; Hamauchi, Natsuki; Hagi, Taisuke; Morohashi, Naoya; Hemmi, Hisashi; Sato, Yukie G.; Saito, Tamao; Yoshimura, Tohru (Frontiers in Microbiology, 2018)
In mammals, D-Ser is synthesized by serine racemase (SR) and degraded by D-amino acid oxidase (DAO). D-Ser acts as an endogenous ligand for N-methyl-D-aspartate (NMDA)- and δ2 glutamate receptors, and is involved in brain functions such as learning and memory. Although SR homologs are highly conserved in eukaryotes, little is known about the significance of D-Ser in non-mammals. In contrast to mammals, the slime mold Dictyostelium discoideum genome encodes SR, DAO, and additionally D-Ser specific degradation enzyme D-Ser dehydratase (DSD), but not NMDA- and δ2 glutamate receptors. Here, we studied the significances of D-Ser and DSD in D. discoideum. Enzymatic assays demonstrated that DSD is 460- and 1,700-fold more active than DAO and SR, respectively, in degrading D-Ser. Moreover, in dsd-null cells D-Ser degradation activity is completely abolished. In fact, while in wild-type D. discoideum intracellular D-Ser levels were considerably low, dsd-null cells accumulated D-Ser. These results indicated that DSD but not DAO is the primary enzyme responsible for D-Ser decomposition in D. discoideum. We found that dsd-null cells exhibit delay in development and arrest at the early culmination stage. The efficiency of spore formation was considerably reduced in the mutant cells. These phenotypes were further pronounced by exogenous D-Ser but rescued by plasmid-borne expression of dsd. qRT-PCR analysis demonstrated that mRNA expression of key genes in the cAMP signaling relay is perturbed in the dsd knockout. Our data indicate novel roles for D-Ser and/or DSD in the regulation of cAMP signaling in the development processes of D. discoideum.